Politik Wacana pada Berita Pilpres 2019 di Media Daring Vivanews.com - Farida Yufarlina Rosita; Marfu'ah Nur Jannah (Program Studi Ilmu Komunikasi, 2020)
This study is intended to identify forms of the 2019 colloquial language expressions in vivanews.com's online media, which focuses on word selections, includes:(a) value-experimentation, (b) relational value and (c) expressive value. The method used is a critical wacana analysis. Research indicates an optional word on the experimental value of the experimental value found in the 2019 online media vivanews.com, where dramatic, powerful, persuasive, and communicative words are used. The wording of a relational value, that is, use of suggestion, a formal word consisting of a foreign vocabulary, and an informal word as a mixture of local languages. And an expressive value choice is more expressing a negative evaluation word. This study also asserted that the use of language is not neutral, but it has hidden interests. By word choice and news content presented, vivanews seemed to expand political support on certain candidates by presenting poorly the opposing candidates. Therefore, research suggests the importance of critical awareness to the reader.